L’Amérique des temps profonds : jalons pour une géo-logique des récits, de John McPhee (Annals of the Former World, 1998) à Herman Melvillle (Pierre, 1852) - Bruno Monfort (Transatlantica)
Since the discovery of so-called “Deep Time,” questions have been raised about the possible invalidation of the category of narrative as a means to account for the immensities of inhuman time at stake in the notion. This article tries to show that what is meant by “narrative” should be specified, depending on whether we are dealing with a retrospective personal narrative or a work of fiction. In Pierre, a novel by Herman Melville, geological data will be used figuratively and not to refer to the experience of an individual, as in John McPhee’s geological travel narratives.